Imaging ectopic fat deposition in caenorhabditis elegans muscles using nonlinear microscopy. Issue 6 (20th April 2015) - Mari, Meropi; Filippidis, George; Palikaras, Konstantinos; Petanidou, Barbara; Fotakis, Costas; Tavernarakis, Nektarios
ABSTRACT: The elucidation of the molecular mechanisms that lead to the development of metabolic syndrome, a complex of pathological conditions including type‐2 diabetes, hypertension, and cardiovascular diseases, is an important issue with high biological significance and requires accurate methods capable of monitoring lipid storage distribution and dynamics in vivo. In this study, the nonlinear phenomena of second and third harmonic generation (SHG, THG) have been employed simultaneously as label‐free, nondestructive diagnostic techniques, for the monitoring and the complementary three‐dimensional (3D) imaging and analysis of the muscular areas and the lipid content localization. THG microscopy was used as a quantitative tool in order to record the accumulation of lipids in nonadipose tissues in the pharyngeal muscles of 18 Caenorhabditis elegans (C. elegans) specimens, while the SHG imaging provided the detailed anatomical information about the structure of the muscles. The ectopic accumulation of fat on the pharyngeal muscles increases in wild‐type (N2) C. elegans between 1 and 9 days of adulthood. This suggests a correlation of ectopic fat accumulation with the process of aging. Our results can contribute to the unraveling of the link between the deposition of ectopic fat and aging, but mainly to the validation of SHG and THG microscopy modalities as new, noninvasive tools to localize and quantify selectively lipid formation and distribution. Microsc. Res. Tech. 78:523–528, 2015 . © 2015 Wiley Periodicals, Inc.